Two men and two women ice fishing at Lake Laberge, Yukon Territory, April 29, 1902. - University of Washington Libraries. Special Collections Division
PH Coll 246.252 [Meed journal: "Netting white fish below the ice (of) Lake Lebarge."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number